Quantitative characteristics and growth hormone gene diversity of thin-tailed sheep in Sitinjau Laut, Kerinci Regency - Rhaphon Seprian. Ht; Depison Depison; Eko Wiyanto (Livestock and Animal Research, 2024)
Objective: This study aims to evaluate the quantitative characteristics and growth hormone gene diversity of thin-tailed sheep in Sitinjau Laut, Kerinci Regency.Methods: The research method used 60 thin-tailed sheep and 60 samples of thin-tailed sheep's blood. The phenotypes observed included: body weight, weight gain, body measurements, and thin-tailed sheep blood samples. The GH gene was identified using the PCR-RFLP method with the Msp1 restriction enzyme. Data analysis included t-test, t2-hotelling, principal component analysis, and allele genotype frequencies.Results: The results showed that body weight, body weight gain, and sizes of male thin-tailed sheep were significantly different (P<0.05) higher than females. The analysis results on the GH|Msp1 gene locus of thin-tailed sheep were monomorphic with one type of allele, namely ++. Conclusions: The average body weight, weight gain, and body measurements of male thin-tail sheep were higher than that of females. The body size characteristic of male and female thin-tailed sheep is the chest circumference, while the body shape characteristic of male and female thin-tailed sheep is the chest depth. The fragmentation of the GH|Msp1 gene in thin-tailed sheep is monomorphic.